Motivation in foreign language learning: a look at type of school environment as a contextual variable - Pavičić Takać Višnja; Berka Nives (ExELL (Explorations in English Language and Linguistics))
Impelled by the observation that motivation might be one of the most important factors within the affective domain influencing foreign language learning (FLL), the field of second language acquisition (SLA) has seen an intense worldwide interest in empirical research in motivational issues. The studies have been rooted in different theories and methodologies, (most notably those advanced by Gardner and Dörnyei and their respective associates) that have given precedence to a number of variables assumed to play an important role in understanding the phenomenon of FLL motivation. The present study is set between the macroperspective of the social-psychological period–by giving a general view of second language motivation–and the situation-specific period–by taking into consideration the immediate learning context. It focuses on exploring the nature of FLL motivation in Croatia at secondary education level where FLL is part of core curriculum. In particular, it explores the role of one specific contextual variable that has been largely ignored in SLA motivational research, i.e. type of school environment, and its interaction with gender and success in FLL.